Pelayanan Perpajakan, Dan Sosialisasi Perpajakan, Terhadap Kepatuhan Wajib Pajak - Bonifasius H. Tambunan (Jurnal Riset Akuntansi dan Bisnis, 2021)
The purpose of this study was to analyze the effect of knowledge of tax regulations, tax services, and tax socialization on taxpayer compliance with sanctions as a moderating variable at the Balige Primary Tax Office. This type of research is causality. The population in this study were individual taxpayers registered at the Balige Primary Tax Office. The sampling method used in this study was nonproability sampling, namely incidental sampling. The type of data used in this study is primary data. The analytical method used is multiple linear regression analysis and interaction test. The results of this study indicate that the knowledge of tax regulations, tax services, and tax socialization simultaneously has a significant effect on taxpayer compliance. Knowledge of tax regulations has a positive and significant effect on taxpayer compliance. Tax services have a positive and significant effect on taxpayer compliance. Tax socialization has a negative effect on taxpayer compliance